Processed silkworm powder (Hongjam) ameliorates metabolic dysfunction-associated steatotic liver disease via GPR35/PKA and SIRT1/AMPK pathways - Lee, Da-Young; Ahn, Hye-Rin; Han, Young-Min; Song, Moon-Young; Lee, Seung-Won; Jang, You-Kyung; Kim, Seokho; Go, Eun-Ji; Kim, Eun-Hee (Frontiers in Nutrition, 2025)
IntroductionMetabolic dysfunction-associated steatotic liver disease (MASLD) is a chronic metabolic disorder linked to obesity, insulin resistance, and type 2 diabetes. This study aimed to investigate the preventive effects of Hongjam, a processed silkworm powder, in a high-fat diet–induced MASLD mouse model and to explore its underlying mechanisms.MethodsC57BL/6J mice were fed a high-fat diet with or without Hongjam supplementation. Serum lipid and glucose levels, hepatic lipid accumulation, liver injury markers, and inflammatory responses were evaluated. Mechanistic analyses focused on SIRT1/AMPK signaling, lipogenic and fatty acid oxidation gene expression, STAT3 phosphorylation, cytokine production, and GPR35/PKA-mediated gluconeogenesis. To identify bioactive components, a silk-derived fibroin peptide was synthesized and tested in palmitate-treated HepG2 cells.ResultsHongjam supplementation improved serum triglyceride, cholesterol, and glucose levels, reduced hepatic lipid accumulation, and lowered liver injury markers. These beneficial effects were associated with activation of the SIRT1/AMPK pathway, suppression of lipogenesis, and enhancement of fatty acid oxidation. Hongjam also attenuated hepatic inflammation by inhibiting STAT3 phosphorylation and reducing pro-inflammatory cytokines, while restoring gluconeogenic capacity through GPR35/PKA signaling. The fibroin peptide suppressed SREBP1 expression, reduced lipid accumulation, and reactivated SIRT1/AMPK and GPR35/PKA/CREB pathways in HepG2 cells.DiscussionThese findings suggest that Hongjam and its fibroin-derived peptide exert protective metabolic effects by modulating lipid metabolism, inflammation, and glucose homeostasis. Together, they highlight the potential of Hongjam as a functional food ingredient for the prevention of MASLD.